Unconventional Metallicity in Graphene Nanoribbons with Armchair Edges. Issue 3 (24th January 2022) - López‐Urías, Florentino; Ortiz‐Medina, Josué
Abstract: Using first‐principles density functional theory calculations, 1D armchair graphene nanoribbons (AGNRs) and graphene with an extended line defect (ELD) mimicking a grain boundary (GB) are investigated. Two AGNRs with n and m indices are laterally coupled, generating an ELD with alternated four‐ and eight‐membered carbon rings. Band structure, electronic density of states, wave functions, scanning tunneling microscope image, and quantum transport are analyzed. Unlike the conventional semiconducting behavior of AGNRs, the authors demonstrated that AGNRs with a 4‐8‐ELD exhibit a metallic behavior for n = m = 3 p + 2 ( p ≥ 0). They further demonstrate that graphene with 4‐8‐ELDs is metallic compared to the semi‐metallic behavior shown by the pristine graphene. Additionally, they investigate the effect of a single vacancy placed at the 4‐8‐ELDs on the electronic properties of AGNRs. The present investigation provides a theoretical basis to tailor graphene structures with possible applications in electronic devices. Abstract : This work presents DFT calculations for two armchair graphene nanoribbons (AGNRs) coupled via an extended line defect (ELD). The ELD consists of alternated four‐ and eight‐membered carbon rings. The coupled ribbons can exhibit metallicity. Also, a vacancy point defect relaxation at the ELD reveals metallicity and ferromagnetism. 2D graphene with alternated coupled AGNRs show metallicity, regardless of the ribbons' width.